The Party : the secret world of China's communist rulers - McGregor, Richard, 1958- (New York, NY : Harper, 2010)
An eye-opening investigation into China's Communist Party and its integral role in the country's rise as a global superpower and rival of the United States.
Maps on lining papers.
Includes bibliographical references and index.
Keywords: Zhongguo gong chan dang; Communist leadership -- China; Communism -- China; China -- Economic policy -- 1976-2000.; China -- Economic policy -- 2000-; China -- Politics and government -- 1976-2002.; China -- Politics and government -- 2002-